Neurodivergence is also an LGBTQ+ topic: Making space for “neuroqueering” in the outdoors - Loy-Ashe, Tarah (Parks Stewardship Forum, 2023)
Recently, the field of research exploring the links between neurodivergence and the LGBTQ+ community has grown. Many queer adults who were not diagnosed as children are just now receiving neurodivergent diagnoses. Nick Walker coined the term “neuroqueer” in 2015 to describe the intersection of being both neurodivergent and queer. “Neuroqueering” refers to the embodying and expressing of one’s neurodivergence in ways that also queer one’s performance of gender, sexuality, ethnicity, and/or other aspects of one’s identity (Walker 2021). Considering the increase of queer representation in the outdoors, it is necessary to also address neuroqueering and its implications for the outdoor community. This conceptual article will address the connection between neurodivergence and the LGBTQ+ community, implications for the queer outdoors, and ways to include neuroqueer recreationalists and outdoor advocates in efforts to make the outdoors more equitable.
Keywords: dept.hls